Basic concepts and definitions of the PAS design and decision system - Monique Arkesteijn (A+BE: Architecture and the Built Environment)
In this chapter, using basic concepts and definitions from management science, decision theory and design methodology, I shall outline the methodological aspects, characteristics and features of the Preference-based Accommodation Strategy (PAS) design and decision system, which I developed for the formation of a corporate accommodation strategy.